ANALISIS SHIFT SHARE UNTUK MENGUKUR PERTUMBUHAN EKONOMI PROVINSI SULAWESI SELATAN PERIODE TAHUN 2013-2017 - Abdul Sumarlin; Muh. Fuad Randy; Muh. Indra Fauzi Ilyas (Jurnal Bisnis dan Kewirausahaan, 2019)
The purpose of this study was to analyze the economic growth of the province of South Sulawesi based on the 2013-2017 shift share approach, then the usefulness of this study could be used by the government in consideration of economic strategy planning in the province of South Sulawesi, as well as in looking at structural shifts economy from year to year, can also provide positive benefits for future studies. There are four sectors that have advantages, namely the agricultural sector of 4,09734751, processing industry of 3,81506411, construction sector of 1,67328785, Wholesale and Retail Trade, Repair of Cars and Motorbikes 2,29588755